Developing Small Scale Chemistry Practicum Module to Identify Students’ Ability in Predict-Observe- Explain (POE) Implementation - Johnsen Harta; Risnita Vicky Listyarini; Fransisca Ditawati Nur Pamenang; Lucia Wiwid Wijayanti; Wonkoo Lee (JKPK (Jurnal Kimia dan Pendidikan Kimia), 2020)
Chemistry practicum does not have to be complicated and requires expensive apparatus and chemicals, and is considered not environmentally friendly. The concept of small scale chemistry practicum is one of appropriate technology that is packaged elegantly to introduce and embed the principles of green chemistry in every chemistry experiments, and also to enhance the concepts of chemistry through verification and scientific discovery. This study aims to create the newest product, the small scale chemistry practicum module to identify the ability of the students of chemistry education study program, Sanata Dharma University, Yogyakarta in formulating predictions on phenomenon based on the insights they have, making direct observations through small scale chemistry practicum, and explaining the results of observations and emphasis on concepts in detail and depth. This research is the development research with the model of Analysis, Design, Develop, Implement, and Evaluate (ADDIE). Data were analyzed by descriptive analysis and Rasch Model. The results of the study show that the product developed has a perfect and feasible level of readability to be tested. From the content aspect, it presented in perfect criteria, as well as the construction aspect and aspect of language, also shows good value. The students already have quite an excellent ability to predict (average score= 76), observe (average score= 88.5), and explain (average score 87.5). Also, it was noted that students enthusiastically applied POE, and the results of POE students show good person reliability value (0.88) in small scale chemistry experiments. The product developed has been valid, effective, and practical for use in experiments according to experts and teachers, and good student responses (Cronbach's alpha value= 0.92) to the product.